2022
DOI: 10.1002/adma.202108266
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ruptured and Nonruptured Aneurysms Using a Semisolid Iodinated Embolic Agent

Abstract: Saccular aneurysms (SAs) are focal outpouchings from the lateral wall of an artery. Depending on their morphology and location, minimally invasive treatment options include coil embolization, flow diverter stents, stent‐assisted coiling, and liquid embolics. Many drawbacks are associated with these treatment options including recanalization, delayed healing, rebleeding, malpositioning of the embolic or stent, stent stenosis, and even rupture of the SA. To overcome these drawbacks, a nanoclay‐based shear‐thinni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Both the control and the FD groups showed increased infiltration of inflammatory cells as evidenced by MPO immunostaining within the thrombus; this is a normal inflammatory response to thrombosis (Figure 5b). [44] In contrast, the FD+GEA group on day 3 revealed GEA uniformly filling the aneurysm sac; thus, excluding the aneurysm from the circulation (Figure 5a,b). At day 14, partial remodeling with biodegradation of the GEA was seen with increased cellular infiltration, predominantly inflammatory cells, as evidenced by high MPO immunostaining.…”
Section: Evaluating Tissue Response To Gea Embolizationmentioning
confidence: 89%
See 2 more Smart Citations
“…Both the control and the FD groups showed increased infiltration of inflammatory cells as evidenced by MPO immunostaining within the thrombus; this is a normal inflammatory response to thrombosis (Figure 5b). [44] In contrast, the FD+GEA group on day 3 revealed GEA uniformly filling the aneurysm sac; thus, excluding the aneurysm from the circulation (Figure 5a,b). At day 14, partial remodeling with biodegradation of the GEA was seen with increased cellular infiltration, predominantly inflammatory cells, as evidenced by high MPO immunostaining.…”
Section: Evaluating Tissue Response To Gea Embolizationmentioning
confidence: 89%
“…[44] Angiographic Imaging in Rats: To assess embolization efficacy, subgroups of rats had femoral artery angiography through the aorta bifurcation prior to necropsy at 7 or 28 days after surgery as previously described. [44] In brief, anesthetized rats were placed supine on an X-raycompatible table. A midline incision was made in the neck to expose and isolate the left common carotid artery.…”
Section: Analysis Of the Flow Dynamics In The Wna Model In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular embolization is a minimally invasive intervention surgery that could selectively deliver embolic agents into the artery to occlude diseased blood vessels. , Owing to its merits of negligible trauma, few complications, and low reoperation incidence as well as rapid recovery, embolization provides a safe endovascular therapy that has been widely applied for treating various diseases in clinics, such as vascular bleeding, unresectable hepatocellular tumors, and aneurysms. Notably, the clinical benefit of embolization therapy was greatly determined by embolic agents. An ideal embolic agent should satisfy the requirements of favorable biocompatibility, stable and complete occlusion in the blood vessels, and appropriate but not uncontrollable swelling ability to match the size of targeted vessels without causing overdosed vascular distension.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Moreover, Stewart et al and co-workers reported an in situ gelling liquid embolic agent based on the polyelectrolytes complex coacervate containing salmine-inositol hexaphosphate, which can transfer from an injectable fluid into a nonflowing solid material by changing ionic concentration. [9a] On the other hand, Oklu et al developed a series of injectable and self-healable shear-thinning hydrogels by simply mixing charged nanoclay with silk, [10] extracellular matrix, [11] lyophilized platelet-rich plasma, [12] and gelatin, [13] respectively. These shear-thinning hydrogels can effectively embolize the porcine renal artery, internal iliac artery, and femoral aneurysm.…”
Section: Introductionmentioning
confidence: 99%